Menstrualotopias: poéticas desde as margens e os devires da subjetividade na literatura de Naty Menstrual - Utrero Zicato, María Florencia (2020)
This study pretends to go through the particular Naty Menstrual’s universe, the first female author self-defined transvestite to publish in Argentina, in the attempt to describe and analyze some of the representations related to the ways transvestite subjectivities as a process become, the ways of “building up” a body, the desire, sexuality, marginality, the violence, the family, the vision upon society and the city, which are present throughout her books Continuadísimo (2008), Batido de Trolo (2012) and Poesía Recuperada (2016). From poststructuralism studies and specially queer studies, I’ll analyze the author’s narrative, as a place that can help us to think, on the one hand, social relationships structured by heterocisnormativity regimes of sex, gender and desire, revealing their violences and exclusions, and on the other hand, the proliferation of narratives and characters from the margins of those discourses, tensing and battling the representations and social imaginaries over the bodies, the flesh, the desires, the pleasures and the city, and the idea of them as places of resistance.